Nano-bio hybrid system for enhanced degradation of cefdinir using Candida sp. SMN04 coated with zero-valent iron nanoparticles - Adikesavan Selvi, Nilanjana Das (Journal of Applied Pharmaceutical Science, 2016)
The present study evaluates the effect of integrated nano-bio hybrid system involving nanoscale zero-valent iron (nFe0) and yeast Candida sp. SMN04 on degradation of cefdinir in aqueous medium. The nanoparticle was chemically synthesised and characterized by atomic force microscopy (AFM), scanning electron microscopy (SEM), EDAX analysis and particle size analyser. Nano-bio hybrid system was prepared using optimal concentration (50 mg/mL) of chemically synthesized nFe0, which were coated on the surface of yeast cells without causing any lethal effects to the cell. The survival and viability of the yeast cells were monitored by AFM and SEM images. Cefdinir (250 mg/L) degradation was studied, in both, the individual and hybrid system. The nano-bio hybrid system showed more effective cefdinir degradation compared to native yeast cell and nano zero-valent iron solely. The adherence of nanoparticles on the surface of the yeast cells increased the permeability of the cell membrane, thereby enhancing the entry of cefdinir into the cell. The kinetic data showed the half-life of cefdinir as 1.34 days for nano-bio hybrid system, 3.99 days for nFe0 and 2.96 days for native yeast, Candida sp. SMN04 confirming that nano-bio hybrid system reduced the half-life to less than half of the time taken by the yeast alone. This study signifies the potential efficacy of the nano-bio hybrid system to serve as an effective remedial tool for the treatment of pharmaceutical wastewater.
Keywords: Cefdinir, Degradation, Nano-bio hybrid, Yeast, Zero-valent iron nanoparticles.